2015
DOI: 10.1016/j.jtemb.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency induces apoptosis via mitochondrial p53- and caspase-dependent pathways in human neuronal precursor cells

Abstract: Previous studies have shown that zinc deficiency leads to apoptosis of neuronal precursor cells in vivo and in vitro. In addition to the role of p53 as a nuclear transcription factor in zinc deficient cultured human neuronal precursors (NT-2), we have now identified the translocation of phosphorylated p53 to the mitochondria and p53-dependent increases in the pro-apoptotic mitochondrial protein BAX leading to a loss of mitochondrial membrane potential as demonstrated by a 25% decrease in JC-1 red:green fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 37 publications
3
34
0
1
Order By: Relevance
“…The early embryonic neuroepithelium appears most sensitive to zinc deficiency. Consistent with our findings of neural cell death, others have shown that reduced zinc conditions lead to cell death of neuroepithelial cells in embryos from wild-type dams given a zincdeficient diet (Dufner-Beattie et al, 2006;Harding et al, 1988), in neuroblastoma and neural progenitor-like cells (Adamo et al, 2010;Nuttall et al, 2015;Seth et al, 2015), in adult neural stem cells (Corniola et al, 2008), and in cortical neurons (Adamo et al, 2010;Ra et al, 2009). Other effects of zinc deficiency include: reduced expression of the neural stem cell marker nestin in embryos and pups from dams fed a severely zinc-deficient diet (Wang et al, 2001); altered neural differentiation of neural precursor cells induced to differentiate with retinoic acid (Morris and Levenson, 2013) and of human induced pluripotent stem cells differentiated to motor neurons (Pfaender et al, 2016); and decreased fetal (rat E19) neural progenitor cell proliferation (Nuttall et al, 2015).…”
Section: Discussion Zinc Is An Essential Nutritional Trace Element Dusupporting
confidence: 92%
“…The early embryonic neuroepithelium appears most sensitive to zinc deficiency. Consistent with our findings of neural cell death, others have shown that reduced zinc conditions lead to cell death of neuroepithelial cells in embryos from wild-type dams given a zincdeficient diet (Dufner-Beattie et al, 2006;Harding et al, 1988), in neuroblastoma and neural progenitor-like cells (Adamo et al, 2010;Nuttall et al, 2015;Seth et al, 2015), in adult neural stem cells (Corniola et al, 2008), and in cortical neurons (Adamo et al, 2010;Ra et al, 2009). Other effects of zinc deficiency include: reduced expression of the neural stem cell marker nestin in embryos and pups from dams fed a severely zinc-deficient diet (Wang et al, 2001); altered neural differentiation of neural precursor cells induced to differentiate with retinoic acid (Morris and Levenson, 2013) and of human induced pluripotent stem cells differentiated to motor neurons (Pfaender et al, 2016); and decreased fetal (rat E19) neural progenitor cell proliferation (Nuttall et al, 2015).…”
Section: Discussion Zinc Is An Essential Nutritional Trace Element Dusupporting
confidence: 92%
“…p53 mediated apoptosis involving mitochondria is critical for cell and one of the trace metal ion Zn, plays a worthy role as Zn deficiency induces p53 expression, thereby initiating apoptotic signal causing loss of mitochondrial membrane potential and p53 dependent caspase activation leading to apoptosis [28]. Also, Zn deficiency induces p53 and oxidative DNA damage [29]. As parkin KD flies were having increased p53 transcript level and oxidative stress, we also analysed Zn level in parkin KD flies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considering the antioxidant properties of zinc, the reduced serum levels of zinc can lead to increased levels of free radicals, oxidative stress, DNA damage, and ultimately cell death. Several studies have shown a correlation between the decrease in zinc level and an increase in the level of oxidative stress, oxidative damage, and cell death (1,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%